Impact of MFS integration for incentive disbursement to distribution representatives: a study on Reckitt (Bangladesh) PLC - Ani, Sumaiya Farhana (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.